Moral Distress and Resilience in the Occupational Therapy Workplace - Annette M. Rivard; Cary A. Brown (Safety, 2019)
Healthcare professionals are inherently vulnerable to moral distress due to their frequent work with persons who are suffering or in crisis, in combination with the strong empathic orientation that underpins the very act of care giving. When accompanied by high workloads, deficiencies in management practices such as low recognition, lack of work autonomy, and/or insufficient opportunity for growth and development, persons in caring professions are at an even higher risk of moral distress. There is evidence that professional resilience is effective in mitigating workplace stress. Successful individual-management of moral distress requires attention to the broader institutional conditions under which these difficulties arise. This paper presents findings from 79 occupational therapists in Alberta and Saskatchewan, Canada, who participated in a survey of moral distress and resilience. On a standardized measure of resiliency their scores fell at the lower end of normal. On a standardized measure of moral distress, the highest levels involved issues of: time to do the job properly, deteriorated quality of care, insensitive co-workers, and unrealistic expectations from others. Nearly 50% reported that they had considered leaving a position due to moral distress. The survey was carried out with the goal of developing a teaching module that included education about moral distress and recommendations for the enhancement of both individual resilience and the construction of resiliency-promoting work environments.